PWE-044 Outcomes In Massive Colorectal Emr, What Should The Patients Know?. (9th June 2014) - Subhani, J; El-Sayed, G
Abstract : Introduction: Data from colorectal endoscopic mucosal resection (EMR) of lesions 6 cm and greater is scant. Endoscopists may welcome these lesions as challenges, but what is the longterm outcome and therefore what should patients be advised before consenting to these procedures? Methods: Prospective data has been collected for over 10 years by a single endoscopist (JMS) on his EMR practice and the database was interrogated for Colorectal resections of flat or sessile polyps, greater or equal to 6 cm. Data for size, Paris classification, assessment, completion in first session, histology, complications (early and late) follow-up duration, recurrence rates and clearance rates. Results: Of 629 lesions on the database, 154 were 40 mm or greater, and 54 lesions in 54 patients were 60 mm or greater. At endoscopy (for the EMR) 5 lesions were clearly invasive cancer and resection was not attempted. Proceeded to resection in 49 lesions (29 LST-G, 13 Is/Isp, 5 IIa + Is, 2 IIa + IIb). 18 resections were stopped with 12 (24%) of these completed at subsequent session. Complications included 1 perforation treated endoscopically (2%), 4 admissions post procedure (8%), no bleeds and 3 late strictures (6%). Of the 49 resections, 19 had not had follow-up at the time of analysis. 5 were awaiting, 10 had been sent to surgery (3 for cancer, 6 benign lesions due to size/position/access, 1 by misinterpreted histology) 4 due to miscellaneous reasons. 30 had endoscopic follow-up, average duration 737 days and 27/30 > 1 year. Recurrence rates at 3 months were 39%, at 1 year were 27 and 80% were eventually endoscopically cleared. Of the 6 patients still not cleared; 2 had <5 mm recurrence at their last endoscopy, 2 >5 mm recurrence and all four of these are awaiting check endoscopy. The final two patients had surgery, one due to complications of a stricture, one due to failure to complete the resection. Overall in these patients 16% had cancer, with most identified before attempted resection. 37 patients avoided surgery, 76% of those with attempted resections. However for 40% of patients this may require multiple endocopies either for the initial resection or treatment of recurrences or complications. Sustained clearance may take as long as a year to achieve. Conclusion: Complications were surprisingly uncommon, although patients should be prepared to be admitted after there initial resection. Bleeds in particular were rare compared to 4.5% seen in lesions (in the database) 20–59 mm in size. This data suggests in experienced hands tackling lesions greater or equal to 6cm endoscopically is worthwhile but patients should be aware that in up to 25% of cases surgery still occurs. If surgery is to be avoided multiple endoscopies maybe necessary for cure. Disclosure of Interest: None Declared.